Quercetin prevents rats from type 1 diabetic liver damage by inhibiting TGF-ꞵ/apelin gene expression - Gholampour Firouzeh; Abbasi Susan; Karimi Zeinab (Current Research in Pharmacology and Drug Discovery)
Background: Hyperglycemia-induced oxidative stress is a significant contributor to diabetic complications, including hepatopathy. The current survey aimed to evaluate the ameliorative effect of quercetin (Q) on liver functional disorders and tissue damage developed by diabetes mellitus in rats. Methods: Grouping of 35 male Wistar rats was performed as follows: sham; sham + quercetin (sham + Q: quercetin, 50 mg/kg/day in 1 ml 1% DMSO for 6 weeks, by gavage); diabetic control (Diabetes: streptozotocin (STZ), 65 mg/kg, i.p.); diabetic + quercetin 1 (D + Q1: quercetin, 25 mg/kg/day in 1 ml 1% DMSO for 6 weeks, by gavage after STZ injection); and diabetic + quercetin 2 (D + Q2: quercetin, 50 mg/kg/day in 1 ml 1% DMSO for 6 weeks, by gavage after STZ injection). Body weight, food intake, and water intake were measured. Ultimately, the samples of plasma and urine, as well as tissue samples of the liver and pancreas were gathered for later assays. Results: STZ injection ended in elevated plasma blood glucose levels, decreased plasma insulin levels, liver dysfunction (increased activity levels of AST, ALT, and ALP, increased plasma levels of total bilirubin, cholesterol, LDL, triglyceride, decreased plasma levels of total protein, albumin and HDL), enhanced levels of malondialdehyde, diminished activities of antioxidant enzymes (superoxide dismutase, and catalase), reduced level of glutathione (GSH) increased gene expression levels of apelin and TGF-ꞵ, plus liver histological destruction. All these changes were diminished by quercetin. However, the measure of improvement in the D + Q2 group was higher than that of the D + Q1 group. Conclusions: Quercetin improved liver function after diabetes mellitus type 1, possibly due to reduced lipid peroxidation, increased antioxidant systems, and inhibiting the apelin/TGF-ꞵ signaling pathway.